Kubernetes native development : develop, build, deploy, and run applications on Kubernetes - Schmeling, Benjamin; Dargatz, Maximilian (Apress, 2022)
Building applications for Kubernetes is both a challenge and an opportunitya challenge because the options and complexity to develop for Kubernetes are evolving rapidly, an opportunity because, if done right, your applications will go into production quicker, scale easier, and run smoother. This book outlines the impact of Containers and Kubernetes on modern software development and discusses the application frameworks to pick from, how to design an application, and how to develop for and on Kubernetes. You are guided through the application life cycle: development, build, and deployment into the runtime phase. In each phase, you see how it ties to Kubernetes and how to leverage its manifold capabilities. Applications will be more lightweight, easier to maintain, and simpler to operate by just focusing on the business logic. This book provides a strong technical foundation in modern software development and operations. Practical examples show you how to apply the concepts and teach you the full potential of Kubernetes. What You Will Learn Get hands-on experience developing, building, and deploying software to Kubernetes Develop your software to get the best out of Kubernetes Focus on business logic while leveraging Kubernetes services Design application components of different granularity from application server-based services to lightweight services Automate deployments and Day 2 operations.